2018
DOI: 10.1080/09637486.2018.1499711
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein source and butyrylated high-amylose maize starch included in a high-protein diet determines the urinary metabolome of rats

Abstract: Intake of red and processed meat increases the risk of colorectal cancer (CRC), whereas dairy product consumption and the intake of dietary fibre are negatively associated with this risk. We investigated the effect of (i) low-protein diets with either whey or cooked meat (beef) as the protein source and (ii) high-protein diets with cooked meat (beef) either without or with the inclusion of 10% butyrylated high-amylose maize starch (HAMSB), on the urinary metabolome of rats. Urine samples from rats were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Abell et al reported different fecal microbial profiles between rats receiving low- or high-amylose maize starch and HAMSB [22]. These results corresponded well with recent findings showing that the inclusion of HAMSB in a high red meat diet, changed the urinary excretion of potentially harmful metabolites derived from the gut microbiota in rats [23].…”
Section: Introductionsupporting
confidence: 75%
“…Abell et al reported different fecal microbial profiles between rats receiving low- or high-amylose maize starch and HAMSB [22]. These results corresponded well with recent findings showing that the inclusion of HAMSB in a high red meat diet, changed the urinary excretion of potentially harmful metabolites derived from the gut microbiota in rats [23].…”
Section: Introductionsupporting
confidence: 75%
“…Whey protein has been characterized as a "fast" digestible protein enriched in leucine, which activates post-prandial protein synthesis and presents beneficial effects on the preservation of lean body mass in older people [22,23]. Urinary metabolic analyzes on Sprague Dawley rats fed a HFD with 15% protein consisting of whey or beef showed lower carnitine, tyrosine and phenylalanine metabolites and creatine/ creatinine excretion as well as higher tryptophan metabolites: so depending on the protein source, the effect on amino-acid metabolism may vary [24]. A recent meta-analysis of 37 randomized controlled trials pooling 2344 individuals reviewed how supplementing whey protein for overweight and obese individuals affected their metabolic syndrome.…”
Section: Whey Proteinmentioning
confidence: 99%
“…The eluent was introduced into an Ultra-High Resolution Qq-Time-Of-Flight mass spectrometer (Impact HD, Bruker Daltonics GmbH, Bremen, Germany) by electrospray ionization in positive and negative mode using the instrumental settings previously described (Najafabadi et al, 2019).…”
Section: Metabolomicsmentioning
confidence: 99%
“…Acquired mass spectra of urine samples were calibrated and peak detection was performed using the Find Molecular Features option in DataAnalysis version 4.2 (Bruker Daltonics GmbH, Bremen, Germany) as previously described (Najafabadi et al, 2019). The data were normalized according to the peak intensity of the internal standard to compensate for variability in sample processing and analytical platform operation.…”
Section: Data Processing and Metabolite Identificationmentioning
confidence: 99%